2016
DOI: 10.1016/j.devcel.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Control of Primary Ciliogenesis by Subdistal Appendages Alters Sensation-Associated Properties of Cilia

Abstract: Vertebrate cells can initiate ciliogenesis from centrioles at the cell center, near the Golgi, forming primary cilia confined or submerged in a deep narrow pit created by membrane invagination. How or why cells maintain submerged cilia is unclear. Here, by characterizing centriole sub-distal appendages (sDAP) in cells exclusively growing submerged cilia, we found that a group of sDAP components localize to the centriole proximal end through the cohesion factor C-Nap1, and that sDAP functions redundantly with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
193
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(217 citation statements)
references
References 49 publications
18
193
4
Order By: Relevance
“…C-NAP1 nulls showed intact centriole structure, as detected by CEP135 and centrin localization, along with apparently normal pericentriolar material, as determined by staining for γ-tubulin (Figure 1, D–F). We noted a loss of ninein signal in one of the separated C-NAP1 centrioles (Figure 1F), which we attribute to the loss of ninein from the centriolar proximal ends while it was being retained at the subdistal appendages, as recently described in another C-NAP1–knockout line (Mazo et al. , 2016).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…C-NAP1 nulls showed intact centriole structure, as detected by CEP135 and centrin localization, along with apparently normal pericentriolar material, as determined by staining for γ-tubulin (Figure 1, D–F). We noted a loss of ninein signal in one of the separated C-NAP1 centrioles (Figure 1F), which we attribute to the loss of ninein from the centriolar proximal ends while it was being retained at the subdistal appendages, as recently described in another C-NAP1–knockout line (Mazo et al. , 2016).…”
Section: Resultssupporting
confidence: 85%
“…Consistent with observations knockouts generated with zinc finger nuclease (ZFN)–mediated targeting of C-NAP1 exon 14 (Panic et al. , 2015) and with a CRISPR-mediated disruption of C-NAP1 exon 20 (Mazo et al. , 2016), 30% of our C-NAP1 nulls showed a distance of ≥2 μm between G1-phase centrioles compared with 5% in wild-type cells (Figure 2, A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15). Interestingly, a recent study reported that the loss of SDA components such as ODF2, CEP170 and Ninein change neither the length of primary cilia nor the percentage of ciliated cells, but affects the spatial configuration of cilia34. In this study, our data also showed that depletion of CCDC120 and CCDC68 changes neither the percentage of ciliated cells nor the ciliary length.…”
Section: Discussioncontrasting
confidence: 54%
“…CEP250 does not seem to be required for primary cilium formation or maintenance [59, 155157], although a recent conflicting report suggests that ciliogenesis cannot proceed if centrosome cohesion is lost [158]. Another recent study showed that CEP250 contributes to retaining the cilium in a submerged state, affecting its capacity to sense external cues [159]. CEP250 appears to be crucial for the recruitment of several proteins to centriole proximal ends, including Girdin (Girders of actin filaments) and a group of proteins that associate also with the distal region of the mother centriole (NEK2, ninein, CEP170, p150glued and KIF2A) [159162].…”
Section: Alms1 Functionmentioning
confidence: 99%